2022
DOI: 10.1136/bjo-2022-322336
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change of peripapillary vessel density and retinal nerve fibre layer thickness in normal tension and primary angle closure glaucoma

Abstract: PurposeTo compare the rates of peripapillary vessel density (pVD) loss and retinal nerve fibre layer (RNFL) thinning in normal tension glaucoma (NTG) and primary angle closure glaucoma (PACG).MethodsBaseline age and severity-matched NTG and PACG eyes (75 eyes of 60 patients for each subtype) were observed longitudinally. All participants’ RNFL thickness were measured by optical coherence tomography (OCT); pVD were measured by swept-source OCT-angiography (OCT-A) and quantified by a customised MATLAB program. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In another prospective study with a longer follow-up duration (2.6 years), Hou et al (2020) reported loss rates of macular VD and GCC thickness that were significantly different from zero in 80 eyes of individuals with POAG. In a retrospective study, Chan et al (2022) reported a peripapillary VD loss rate of −1.65%/year and an RNFL thinning rate of −0.25 μm/ year in 75 NTG eyes; however, only the peripapillary VD loss rate differed significantly from zero. Our results are similar with those of the previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In another prospective study with a longer follow-up duration (2.6 years), Hou et al (2020) reported loss rates of macular VD and GCC thickness that were significantly different from zero in 80 eyes of individuals with POAG. In a retrospective study, Chan et al (2022) reported a peripapillary VD loss rate of −1.65%/year and an RNFL thinning rate of −0.25 μm/ year in 75 NTG eyes; however, only the peripapillary VD loss rate differed significantly from zero. Our results are similar with those of the previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…In a retrospective study, Chan et al. (2022) reported a peripapillary VD loss rate of −1.65%/year and an RNFL thinning rate of −0.25 μm/year in 75 NTG eyes; however, only the peripapillary VD loss rate differed significantly from zero. Our results are similar with those of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Chan et al. (2022) compared the longitudinal changes in peripapillary vessel density (pVD), encompassing both large vessels and capillaries, between NTG and PACG. They observed faster rates of pVD reduction in NTG eyes when compared to PACG despite both groups showing similar rates of VF MD loss and RNFL thinning.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis to explain these variations is that microcirculatory insufficiency may play a prominent role in the pathogenesis of glaucoma in NTG (Leung & Tham, 2022). In contrast, it is conceivable that PACG or POAG, particularly high‐tension glaucoma, may rely more heavily on IOP as a driving force (Chan et al., 2022; Gazzard et al., 2003).…”
Section: Discussionmentioning
confidence: 99%